An absence of accountability: Evidence of employers’ failure to measure and manage employee health benefits administration - Singer, Sara J.; Pfeffer, Jeffrey; Nikolov, Margaret C. (Social science & medicine (1982), 2025)
Because employers provide health benefits to >50 % of the working age U.S. population, benefits managers at companies who purchase and potentially oversee design and delivery of health benefits have an important role in affecting healthcare delivery. We sought to assess how companies measure and manage health benefits, because these dimensions of accountability affect the performance of the health ecosystem. We randomly sampled companies and obtained data from >200 people knowledgeable about health benefits administration in their organizations. Our novel survey comprehensively inquired about what data concerning health benefits operations companies collected and who, if anyone, was responsible for aspects of employee benefits experience and outcomes. We found a surprisingly small amount of accountability for employer-provided health benefits. For instance, 39 % of companies never requested any feedback from their employees about their health benefits, just 6 % assessed the time employees spent getting questions about their health benefits answered, and <5 % of companies measured how often employees postponed filling a prescription or seeing a doctor because of cost. Moreover, there was a widespread absence of accountability for the performance of health plans. On average, 64 % of 15 health benefits performance dimensions were managed by no one, and more than half of respondents reported that no one in their organizations was held accountable for either the physical (64 %) or emotional (59 %) wellbeing of the workforce. Companies mostly provide minimal oversight of the health plans they provide to their employees. This lack of accountability is inconsistent with employers’ responsibilities to effectively manage the benefits they provide and almost certainly contributes to the well-documented problems of employee dissatisfaction with third party health benefits administrators and the frustration and wasted time spent accessing care and reimbursement that occasionally results in care delayed or denied, with consequences for both behavioral and physical health. •Employers are doing an inadequate job of measuring and managing health benefits.•64 % of 15 health benefits performance dimensions were managed by no one.•39 % of companies never requested any employee feedback about health benefits.•Lack of accountability is inconsistent with employer responsibilities for benefits.•This affects employees access to care and satisfaction with plan administrators.